Developments in The EU-German Judicial Love Story: The Right To Be Forgotten II - Ana Bobić (German Law Journal, 2020)
The relationship between the Court of Justice and the Bundesverfassungsgericht is perhaps one of the most explored relationships in all of EU’s legal history. In attempting to understand and operationalize the uncertainty surrounding the positioning between EU and national constitutional orders, they have in some respects followed the footsteps of a typical life-long love story: in the early years of European integration, both courts appeared to be in denial of any romance, and entered into a conflict over the question of the final arbiter; they subsequently turned to flirting by moving away from an institutionally based conflict towards finding a common substantive ground; which resulted in finally abandoning the competition for domination, but rather embracing mutual respect and a heterarchical relationship. This brief piece follows these developments in fundamental rights review that for now end with the second German decision concerning the right to be forgotten.